Dimensions of Informal Sector Association Membership: Experiences from Jua Kali Associations in Western Kenya - Juepner, Anne G.; McCormick, Dorothy; Ng'ethe, Njuguna (Advances in Social Sciences Research Journal, 2018)
This article explores the various dimensions of membership of informal sector entrepreneurs in business associations they ostensibly formed to pursue their needs and strategic interests. It is based on a case study of Jua Kali Associations (JKAs) in Homa Bay Town in Western Kenya using Hirschman's concept of exit, voice and loyalty as the theoretical frame and data generated and analysed through a qualitative research design. The broad spectrum of membership dimensions ranging from active membership, to dormant membership and non-membership are being examined. The analysis points to certain factors that influence decisions of informal sector entrepreneurs to what degree they engage in their associations. The study further shows that there are jua kalis who decided not to join any association in the first place. Only very few jua kalis took the conscious decision to exit their associations (often due to disappointment and frustration) leading to ‘open exit’. The study concludes that exit is multifaceted and that this experience merits attention since it contributes to the fact that only a very small number of all informal sector entrepreneurs operating in Homa Bay Town were JKA members utilizing the associations in pursuit of their organized voice.